Carbon emission quota allocating on coal and electric power enterprises under carbon trading pilot in China: Mathematical formulation and solution technique. (1st December 2019) - Wang, B.J.; Zhao, J.L.; Wei, Y.X.
Abstract: This paper considers the fair and efficient principles, a fairness deviation index model was established based on measurement of carbon emissions in various links inside the coal power supply chain enterprise in consideration. Meanwhile, a carbon quota allocation model was built by taking minimum fairness deviation index as the objective and department production levels inside various links as constraint conditions under the carbon trading pilot program. Furthermore, from the angle of inter-link coordination of the coal power supply chain enterprise, carbon quotas in different links were coordinated with total emission quantity and tradability of the enterprise's carbon quota taken as objectives. X coal power supply chain enterprise taken as an example, its carbon emission reduction responsibilities in raw coal mining, coal washery and various power generation links during 2018–2020 were internally decomposed under constraints of total carbon emission and emission reduction objective. Study conclusions provide a theoretical support and corresponding policy basis for internal and external coordination between coal and electric power enterprises in carbon emission reduction under the carbon quota constraint.